(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Public Service Motivation has gained traction among public administration scholars ever since Perry provided a measurement scale to account for the motivation profile of public service employees. However, the PSM as we know it today is primarily the product of western scholarship